2015
DOI: 10.1155/2015/703424
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cardiac Metastasis from Uterine Cervical Carcinoma

Abstract: Cases of cardiac metastasis from uterine cervical carcinoma are rare. While they are occasionally found on autopsy, antemortem recognition is extremely rare. We confirmed a case of cardiac metastasis from cervical carcinoma antemortem, because we observed a decrease in platelet count during the course of treatment. The patient was a 27-year-old woman diagnosed with stage Ib1 uterine cervical carcinoma. Radical hysterectomy with pelvic lymphadenectomy was performed. Para-aortic lymph node metastasis was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(8 reference statements)
1
8
0
Order By: Relevance
“…Although the surgery seems to be the best option at the moment 6 . The prognosis of cardiac metastasis is poor with an average life expectancy less than six months after diagnosis 7 . In our case, ECG showed characteristic abnormality.…”
Section: Discussionmentioning
confidence: 54%
“…Although the surgery seems to be the best option at the moment 6 . The prognosis of cardiac metastasis is poor with an average life expectancy less than six months after diagnosis 7 . In our case, ECG showed characteristic abnormality.…”
Section: Discussionmentioning
confidence: 54%
“…Intracavitary masses are very rare and are usually right-sided. Most common primary tumor origins of cardiac metastases include melanoma, lung, breast, and lymphoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the clinically silent nature of these metastases. The most common symptoms when present include chest pain, arrhythmias, cardiac tamponade, recurrent pulmonary emboli, cardiac failure, and pulmonary hypertension [5]. Echocardiography is the first-line imaging modality in the detection and evaluation of cardiac tumors with the ability to observe location, shape, mobility, and other features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of cardiac metastasis is poor with an average life expectancy less than 6 months after diagnosis ( 8 ). In the review of 37 cases by Okamoto et al, in which cardiac metastasis from cervical carcinoma was found before death, chest symptoms were seen in 81.5% of the patients (8).…”
Section: Discussionmentioning
confidence: 99%